PENGARUH PAPARAN SITUS JEJARING SOSIAL FACEBOOK TERHADAP SIKAP SEKSUAL REMAJA DI KOTA SEMARANG - Rahmawati, Agustin; Kusumawati, Ema (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Youth is a period of transition between childhood and adult, where the growth spurt occurs, arising secondary sexual characteristics, the achievement of fertility, and changes occur and cognitive psychology. The problem that often stands out among teenagers is still about TRIAD KRR include sexuality (premarital sex, unwanted pregnancy, abortions), sexually transmitted infections (STIs), HIV and AIDS and drug abuse. (Muadz Masri, 2009). From some online media such as vivanews and detikcom to review about issue of social networking as in the last one year period mentioned prostitution involving children in social networking teens and junior high school. Purpose to know how influence of facebook exposure as social network site toward sexual attitudes in adolescent semarang city.Â  Methods: This study using analytic correlational study. This study used a cross-sectional approach or cross-sectional study. A large sample of 374 students of SMAN in Semarang.Â  Based on the results of statistical tests using correlation chi square p value of 0.814 (p> 0.05) there was no significant correlation between the intensity of the use of facebook with adolescent sexual attitudes, p value of 0.019 (p> <0.05) there is a correlation between motifs use facebook with adolescent sexual attitudes, the p value of 0.000 (p> 0.05) there is a correlation between the use of facebook with adolescent sexual attitudes, the p-value of 0.000 (p <0.05) there was a correlation between self-consciousness / awareness of the use of facebook with adolescent sexual attitudes. Variable self-consciousness / awareness is the most powerful influence on adolescent sexual attitudes with p value = 0.000. Adolescents who have high awareness / awareness of the possibility of having a facebook account to be 2.1 times more permissive to seksuality than adolescents who have low awareness of the facebook account. Keyword: facebook, attitude